Forecasting Coal Consumption Reduction for Climate Change - Baginda Parsaulian; Aidil Alfin; Zirah Eka Risandani Nasution (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This study uniquely examines how reducing coal consumption could mitigate climate change and help achieve the Sustainable Development Goals by 2030. Research Objectives: This study investigates the impact of reducing coal consumption on climate change and on achieving the Sustainable Development Goals in Indonesia, a major coal exporter, as well as in China and India, which are expected to become major coal importers by 2030. Research Methods: This study employs a basic panel regression model to analyze data from 2015 to 2024, and uses an ARIMA method to forecast progress toward the Sustainable Development Goals by 2030. Empirical Results: The findings highlight the urgent need for Indonesia, China, and India to shift to clean, renewable energy to meet the Sustainable Development Goals by 2030, which aim to reduce emissions. Implications: This study recommends that the governments of Indonesia, China, and India should increase their use of renewable energy sources more consistently. JEL Classification: O1, O13, O130, O21, O210